To solve the equation \( x - \frac{7}{8} = -5 \) for \( x \), we can add \( \frac{7}{8} \) to both sides of the equation.
Here’s how it looks:
\[ x - \frac{7}{8} + \frac{7}{8} = -5 + \frac{7}{8} \]
This simplifies to:
\[ x = -5 + \frac{7}{8} \]
Now, to combine \(-5\) and \(\frac{7}{8}\), we can convert \(-5\) to a fraction with a denominator of 8.
\(-5\) can be rewritten as \(-\frac{40}{8}\):
\[ x = -\frac{40}{8} + \frac{7}{8} \]
Now, combine the fractions:
\[ x = \frac{-40 + 7}{8} = \frac{-33}{8} \]
So, the value of \( x \) is \( -\frac{33}{8} \).
To summarize, you should add \( \frac{7}{8} \) to both sides of the equation to find the value of \( x \).